1999
DOI: 10.1046/j.1365-2788.1999.00219.x
|View full text |Cite
|
Sign up to set email alerts
|

Fragile‐X syndrome, Down’s syndrome and autism: awareness and knowledge amongst special educators

Abstract: Fragile-X syndrome is the commonest cause of inherited intellectual disability. There is good evidence for a behavioural phenotype. This has implications for school staff using standard educational techniques. Similarly, autism is known to create particular educational requirements. The present study examined the awareness and knowledge of fragile-X syndrome, Down's syndrome and autism amongst staff in special and mainstream education. One hundred and two special school staff and 40 mainstream school staff com… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
20
0
1

Year Published

2007
2007
2020
2020

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(22 citation statements)
references
References 24 publications
1
20
0
1
Order By: Relevance
“…Cognitive defects in those afflicted with DS include delayed speech and language development, and impairments in spatial and long-term memory. Roughly 5–10% of individuals with DS meet the diagnosis criteria for autism spectrum disorder [3840], though diagnosis can be difficult in patients with severe ID. Most cases of the disorder are caused by a complete trisomy of chromosome 21 (HSA21), though there are rare cases of DS caused by partial trisomies in the long arm of HSA21, deemed the DS critical region (DSCR) [41].…”
Section: Spine Dysgenesis In Autism Related Disordersmentioning
confidence: 99%
“…Cognitive defects in those afflicted with DS include delayed speech and language development, and impairments in spatial and long-term memory. Roughly 5–10% of individuals with DS meet the diagnosis criteria for autism spectrum disorder [3840], though diagnosis can be difficult in patients with severe ID. Most cases of the disorder are caused by a complete trisomy of chromosome 21 (HSA21), though there are rare cases of DS caused by partial trisomies in the long arm of HSA21, deemed the DS critical region (DSCR) [41].…”
Section: Spine Dysgenesis In Autism Related Disordersmentioning
confidence: 99%
“…In particular, IQ and other indices of more specific cognitive functions are predicted by measures of the home environment (such as enrichment opportunities and economic status) for boys [Dyer-Friedman et al, 2002;Glaser et al, 2003] and girls [DyerFreidman et al, 2002] with the full mutation. At the same time, there is evidence that challenging child behaviors and a lack of social and professional support, as well as maternal premutation vulnerabilities, lead to lower levels of psychological wellbeing among some mothers [Roy et al, 1995;York et al, 1999;Bailey et al, 2000b;Johnston et al, 2003;Poehlmann et al, 2005] and thus, perhaps, a less than optimal environment within which their children with FXS must learn language [Murphy and Abbeduto, 2005].…”
Section: Within-syndrome Variabilitymentioning
confidence: 99%
“…A study conducted in Great Britain investigated what educators in both the mainstream ( n  = 102) and special needs ( n  = 40) sectors knew about disorders like ASD [16]. The study found that 99% of the special needs educators and all of the mainstream educators knew what ASD was [16].…”
Section: Introductionmentioning
confidence: 99%